Numerical simulation for salinity intrusion measurement models using the MacCormack finite difference method with lagrange interpolation - Kulmart, Khemisara; Pochai, Nopparat (My University, 2020)
This study aims to develop numerical simulation of one-dimensional advection- diffusion equation. We propose two different methods for salinity intrusion measurement in a stream. In the first method, the forward time centered space (FTCS) is used. In the second method, the MacCormack scheme is applied. The results from these methods can be used as salinity intrusion measurement compared with the first set of exact numbers. Then, we interpolate function at left boundary by using the MacCormack scheme compared with the second set of exact numbers. The results prove that the interpolate function can actually be used. Moreover, the parameters are used and tested with technique of the MacCormack Scheme in order to simulate salinity intrusion measurement methods. After comparing results of both methods with the first set of exact numbers, we found that the MacCormack scheme is the most suitable method.
Keywords: 65N06; Finite difference method; Forward time centered space (FTCS); Salinity intrusion; The MacCormack scheme